1989
DOI: 10.1093/oxfordjournals.humrep.a136878
|View full text |Cite
|
Sign up to set email alerts
|

The endometrial cycle: the expression of a secretory component correlated with the luteinizing hormone peak

Abstract: This paper reports the pattern of production and secretion of a secretory phase epitope in the endometrium of 44 normal fertile women. Peroxidase immunochemistry was used to detect the monoclonal antibody D9B1, which binds to a peptide-associated sialylated oligosaccharide, in endometrial biopsies all chronologically dated from the luteinizing hormone (LH) peak. During the proliferative phase, the epitope was shown to be absent from tissue sections. It first made its appearance within gland cells 2 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Within single specimens of endometrium we also observed variation in the level of epithelial CD44. This is consistent with previous studies in which we have demonstrated heterogeneity in cell surface-associated components within the gland cell population [40,[43][44][45]. The tissue used in this study showed normal histology, and its timing was in the phase expected on the basis of the last menstrual period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within single specimens of endometrium we also observed variation in the level of epithelial CD44. This is consistent with previous studies in which we have demonstrated heterogeneity in cell surface-associated components within the gland cell population [40,[43][44][45]. The tissue used in this study showed normal histology, and its timing was in the phase expected on the basis of the last menstrual period.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a high potential for glycosylation, and CD44-associated glycans can therefore be expected to contribute to the endometrial glycocalyx. We have shown that alterations in the glycosylation patterns of epithelial cell surface and secretory glycoproteins occur in endometrium during the menstrual cycle [44,45,47,48]. CD44 glycans have been implicated in binding and presentation of growth factors and in cell motility in other cell types [27,49].…”
Section: Discussionmentioning
confidence: 99%
“…Human endometrial epithelium undergoes progesterone-modulated differentiation during menstrual cycle [33,34]. The qualitative and quantitative changes in the secretion of the endometrium are associated with the proliferation of glandular epithelium with increased golgi and secretory apparatus [35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for example, Thor et al [16] report that as many as 60% of glands lack the sialyl T n epitope in midsecretory phase, while keratan sulphate is absent from about 20% of glands at the same stage [18]. Secondly, although the general features of glycan up-regulation are consistent with an effect of progesterone, there are subtle differences in the timing of the appearance of different structures: sialyl T n [16] and keratan sulphate [18,19] appear in the early secretory phase (beginning 2 days after ovulation), while DBA binding sites appear 3 days later, in the mid-secretory phase [23a].…”
Section: Localization Of Glycans Recognized By Dba In Endometrium Fromentioning
confidence: 99%